Assessment of drought hazards and their correlations on land use land cover change using multiple geospatial indices : the case of the Lower Songkhram River Basin - Phorntip Saensri; Ho Huu Loc; Shrestha, Sangam; Shanmugam, Mohana Sundaram; Pal, Indrajit; Kurita Water and Environment Foundation, Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
For centuries, the threat of drought has been a significant concern for mankind as its devastating prolonged duration and wider impact on larger communities. Lower Songkhram River Basin is located in the Northeastern part of Thailand. LSRB has been identified as vulnerable to drought hazards. Therefore, the present study aims to understand the drought hazards and their potential correlations on land use land cover (LULC) change across LSRB using geospatial indices (GIs), NDVI, NDSI, and NDWI, during the period of 1991-2021. The results indicated that hydrological drought has increasingly become the dominant type of drought since the 2010s. These conditions persisted until 2021 and have significant impacts on land use, land cover, compared to meteorological drought and leading to great threatened and stuffed people's livelihoods. The study used Pearson Correlation Coefficient (PCC) to analyze the time lag response of GIs to droughts, showing that meteorological drought had the strongest impact during the drought year, while hydrological drought had a prolonged severe impact for up to 5 years. Therefore, land use land cover change detections were performed during 2010-2015 and 2015-2019 to determine corresponding impacts on hydrological drought. We found a significant extension in agricultural cultivation; high water consumption like para rubber has been promoted by the national plan. Despite the most severe drought events, socioeconomic factors are the main factors to control LULC change. Therefore, stressors on water deficits and insufficient quality of agricultural yield are considered a pressing concern. Lastly, the proposed Natural-based Solutions (NbS), wetland preservation, and reforestation have been thoroughly identified as appropriate measures for mitigating the risk of over-dried threat of prolonged drought. Our research offers valuable insights into understanding drought and its mechanism, along with potential solutions that could have highly beneficial for policymakers and local people.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Droughts -- Thailand -- Lower Songkhram River Basin; Hydrologic models -- Thailand -- Lower Songkhram River Basin; Land cover -- Thailand -- Lower Songkhram River Basin; Land use -- Thailand -- Lower Songkhram River Basin